Two new species of the genus Nigrobaetis Kazlauskas (in Novikova & Kluge), 1987 (Ephemeroptera: Baetidae) from Southwest China - Li, Bo; Shi, Weifang; Li, Xianfu; Tong, Xiaoli (Zootaxa, 2023)
Two new species of Nigrobaetis Kazlauskas (in Novikova & Kluge), 1987 are described from Southwest China: Nigrobaetis bilongus sp. nov. based on larval and imaginal materials which are reared from larvae; Nigrobaetis trialbus sp. nov. based on larval stage.